(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the prevalence of cervical cancer and connect it with demographic variables among women who presented at the Farooq Hospital / Akhtar Saeed Medical College, Rawalpindi, with a history of abnormal vaginal bleeding. Study Design: A descriptive cross-sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynaecology at Farooq Hospital / Akhtar Saeed Medical College, Rawalpindi from July 15, 2022, and July 15, 2023. Materials and Methods: A number of clinical and demographic variables were evaluated, such as age, parity, and amount of time from beginning of symptoms. The existence of cervical cancer was established by tissue biopsies and histopathology. To examine statistical significance, the Chi-square test was used. Results: The average age of the population was 39.12 years, ±4.35 years. The mean SD time from the onset of symptoms was 8.14 months (interquartile range: 3–11). 50 patients, or 20% of the total, were between the ages of 17 and 25. A greater percentage of patients (45.60%) were between the ages of 26 and 35. Those that were left behind (34.40%) were between the ages of 36 to 47 years. 36% of women had one or two children, 28% had three or more, and the remaining 24% had five or more. Only 12% of women had no children. Of the 250 women, 39 (15.6%) had cervical cancer that was determined by biopsy and histology of the cervical tissue. The duration of the presenting symptoms and parity were not statistically significant (P = 0.130 and 0.455, respectively), whereas age was (P = 0.004). Conclusion: Women with a history of irregular vaginal bleeding had a 15.6% risk of cervical cancer. Age showed a substantial correlation with the probability of being diagnosed with cervical cancer, highlighting the need of agespecific screening approaches and attentiveness in gynaecological evaluations.